COMPREHENSIVE MIDWIFE CARE IN MRS. "R" G2P1A0 SWELLING IN THE LEGS WITH HYDROTHERAPY - Fatonah, Sofa; Sri Wulan Suci, Chelvi; Mujiwati, Sri; Yuliana, Yuliana (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Swelling in the legs is one of discomforts that often occurs in third trimester pregnant women. Swelling of the legs occurs in about 80% of third trimester pregnant women, this condition is caused by uterine compression which inhibits venous return and the pull of gravity causing an increase in fluid retention, so that it requires care to reduce swelling in the feet, namely by doing hydrotherapy that you can do at home. According to the survey results during practice at Clinic "A" from January-February 2022, 128 pregnant women who made antenatal care (ANC) visits, 92 pregnant women in the third trimester, and 10 third trimester pregnant women who experienced swelling in their feet and did not know the cause. how to treat the swollen feet. The purpose of this case study is to be able to provide comprehensive midwifery care to Mrs. “R” G2P1A0 swelling in the feet with hydrotherapy at the clinic “A” Banjaran in 2022. Methods. The research method used a case study approach that was carried out on Mrs. “R” G2P1A0 started from 37 weeks 4 days of gestation until the mother used contraception. Results & Analysis. The results of the case studies carried out were giving the hydrotherapy care for 4 weeks with 5 times a week giving hydrotherapy with a frequency of 10 minutes, the water temperature was 380C, so that the mother felt more comfortable and the swelling in the feet that she experienced was reduced. Discussion. The conclusion of this case study is that after hydrotherapy for 4 weeks with 5 times of hydrotherapy, the frequency of 10 minutes at 380C water temperature reduced the swelling that the mother experienced. It is recommended to clinic "A" to be able to implement this hydrotherapy care as an effort to reduce the discomfort of the third trimester.